(untitled) (Fenestella. Inside Medieval Art, 2021)
The paper is dedicated to the stylistic and iconographic analysis of some sculpted lintels decorating the portals of the churches of Piacenza, one of the most lively places in the northern Italian artistic scene of the 12th century. The legacy of the works created for the city’s cathedral by Nicholaus’ workshop is echoed in the reliefs of the churches of San Matteo, Sant’Ilario and the previously unseen portal of Santo Stefano. Through the study of the surviving historical evidence, the comparison with works from the same period and context and a renewed focus on iconographic content, the aim of the paper is to demonstrate the symbolic significance of the representations on the architraves. Particular attention is paid to the unusual iconography of the ‘Incredulity of Saint Thomas’ on the portal of the church of Sant’Ilario. The attempt to reread the inscriptions and the framing of this work in the socio-cultural context of Piacenza in the late 12th century allows us to formulate new hypotheses on the connection between iconographic choices, instances of spiritual renewal of society and liturgical rituals, underlying the creation of sculptures that significantly decorate the doors of access to sacred places, ways of salvation for the faithful penitents.